PENGARUH PENILAIAN PRESTASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. DILIA UTAMA PALEMBANG - Herman Efrizal; Suharti . (JURNAL KOMPETITIF, 2017)
This research aims to know is there any influence the assessment of the achievements of the work and the working  environment are partial and simultaneous performance against PT.Major Dilia Palembang.The population in this research is the main employees of PT.Dilia Palembang That add up to 30 employees.The samples on this research as many as 30 respondents,where sampling techniques using saturated (census). In this study,the method  of analisys using multiple linear regression.The results of this study showed a regression equation that is formed is Y = 0,547 +0,473 X1 +0,385 X2+ e, with a value of R (correlation) of 0,860, meaning that the relationship between the Achievements Appraisal Variables work and work and work environment very closely and direction of 86 %. As for thevalue of the coefficient of determination of 0,720.These results are statistically very significant meaning 72,00 % collectively can account for the influence of the work achievement assessment variables (X1) and the work environment (X2) against variable Employee Performance,while the rest is 28,00% can be explained by other factors that are not listed in this research.Keywords : assessment of the achievements of the work,the work environment and employee performance.